Application of antimicrobial sonodynamic therapy as a potential treatment modality in dentistry: A literature review - Maryam Pourhajibagher; Rashin Bahrami; Abbas Bahador (Elsevier, 2024)
The accumulation of dental plaque is a precursor to various dental infections, including lesions, inflammation around dental implants, and inflammation under dentures. Traditional cleaning methods involving physical removal and chemical agents often fall short of eliminating bacteria and their protective biofilms. These methods can also inadvertently lead to bacteria that resist drugs and upset the mouth's microbial harmony. To counter these issues, a new approach is needed that can target and clear away dental plaque, minimize biofilms and bacteria, and thus support sustained dental health. Enter antimicrobial sonodynamic therapy (aSDT), a supplementary treatment that uses gentle ultrasound waves to trigger a sonosensitizer compound, destroying bacterial cells. This process works by generating heat, mechanical pressure, initiating chemical reactions, and producing reactive oxygen species (ROS), offering a fresh tactic for managing dental plaque and biofilms. The study reviews how aSDT could serve as an innovative dental treatment option to enhance oral health.